1982
DOI: 10.1002/jat.2550020109
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone treatment of acute alcoholic or benzodiazepine intoxication

Abstract: Naloxone (0.8–1.6 mg i.v.) effectively counteracted the clinical signs associated with benzodiazepine intoxication in 9 out of 10 emergency room patients. Naloxone (0.8–2.8 mg i.v.) also favorably influenced the state of consciousness in 9 out of 9 alcohol‐intoxicated patients. In cases of acute narcotic overdose, the action of naloxone is almost immediate. Since a longer time was required for naloxone to counteract benzodiazepine or alcohol intoxication, the mechanism of action may be different from that impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…4,5,11 In addition, there are limited studies on the assessment of naloxone effects on benzodiazepines poisoning. Some old studies in 70s and 80s have shown that naloxone can be used in benzodiazepine poisoning, [6][7][8][9][10] and it has relative effects on disappearing of anxiolytic function and decreases consciousness level of diazepam, 12,13 but some other studies in those years could not prove this beneficial effects of naloxone. 14,15 After that, no valuabe human studies have been done in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,11 In addition, there are limited studies on the assessment of naloxone effects on benzodiazepines poisoning. Some old studies in 70s and 80s have shown that naloxone can be used in benzodiazepine poisoning, [6][7][8][9][10] and it has relative effects on disappearing of anxiolytic function and decreases consciousness level of diazepam, 12,13 but some other studies in those years could not prove this beneficial effects of naloxone. 14,15 After that, no valuabe human studies have been done in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone has had beneficial effects in some of these studies, while it has had no effects in others. [6][7][8][9][10] Hence, the aim of this study was assessment of naloxone effects in patients with benzodiazeoines poisoning, who were referred to the Loghman Hakim Poisoning hospital in Tehran.…”
Section: Introductionmentioning
confidence: 99%